PENGARUH REBUSAN BUNGA ROSELLA (HISBISCUS SABDARIFFA) TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Wijaya, I Putu Artha (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2020)
Introduction: Hypertension is a condition of increased blood pressure above normal which is 120/80 mmHg, this is a disease that is categorized as the silent killer disease, because many sufferers do not know that they have hypertension. Hypertension can be prevented by using non-pharmacological treatments is the stew of rosella flowers (hisbiscus sabdariffa) where rosella flowers can reduce blood pressure due to the presence of active ingredients namely anthocyanin, phenolic, threonine, leucine, valine, glycine and ascorbic acid. Objectives: to determine the effect of rosella stew (hisbiscus sabdariffa) on blood pressure in hypertensive patients in Sulangai banjar, Sulangai Village. Method: This research is a pre-experimental study with one group pre-test and post-test design with sampling technique in this study using total sampling, the sampling technique where the number of samples is equal to the population of 33 people. Results: Wilcoxon Signed Rank Test analysis results obtained p value = 0.001 on the pre-test and post-test blood pressure which means the value of p <0.05 Conclusion: There is an Influence of Rosella (Hisbicus sabdariffa) Stew on Blood Pressure Decrease in Banjar Sulangai, Sulangai Village.